VARIABILITAS GENETIK DAN HERITABILITAS KARAKTER AGRONOMIS BEBERAPA GENOTIPE SORGUM MANIS (Sorghum bicolor L. Moench) KOLEKSI BATAN - ', Sugianto; ', Nurbaiti; ', Deviona (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aims to determine the genetic variability and the heritability character of agronomic some sweet sorghum genotype (Sorghum bicolor (L.) Moench) collection of BATAN. This research has been conducted in Field Experiment and the plant breeding laboratory, Faculty of Agriculture, University of Riau from April 2013 to September 2013. This inquiry has been carried on experiments using a randomized block design (RBD) consist of 13 treatments and 3 replications that contained 39 experimental units. Treatment consists of 13 genotypes, there are Patir-1, Patir-2, Patir-3, Patir-4, Patir-5, Patir-6, Patir-7, Patir-8, Patir-9, Patir-10, Kawali, Mandau and Pahat. The outcome showed that Patir-9 was the genotype with the best result because it bears a weight of seeds per panicle, 1000 grain weight and output per m2 higher than other genotypes. Plant height and panicle length wide genetic variability, whereas the other theatrical roles suffer a narrow variability. Characterization of plant height, number of leaves, number of segments per plant, dry weight, panicle length, grain weight per panicle and yield per m2 has a high heritability value, a character who receives a moderate heritability value   that stem diameter and weight of 1000 seeds, while the fiber takes in low heritability values   were age flowering. Keywords: Sorghum, Genotype, Genetic variability, Heritability